Sydney Declaration on Predatory or Pseudo Journals and Publishers - 2024, APAME (Journal of the ASEAN Federation of Endocrine Societies, 2024)
This declaration was launched at the 2024 Convention of the Asia Pacific Association of Medical Journal Editors (APAME) held in New South Wales, Australia from 28 to 30 August 2024. It is concurrently published in Journals linked to APAME and listed in the Index Medicus of the South-East Asia Region (IMSEAR) and the Western Pacific Region (WPRIM).